Temporal trends and future projections of incidence rate and mortality for asthma in China: an analysis of the Global Burden of Disease Study 2021 - Xi Chen; Xi Chen; Dandan Ma; Hangyu Li; Yilin Liu; Guixing Xu; Xinyu Deng; Qi Li; Junqi Li; Hui Pan (Frontiers in Medicine)
BackgroundAsthma poses a significant public health burden in China, affecting millions with substantial incidence and mortality. Understanding the trends and future projections of asthma incidence and mortality is crucial for healthcare planning.MethodsWe analyzed asthma incidence and mortality data sourced from the Global Burden of Disease (GBD) 2021 study from 1990 to 2021, calculated the age-standardized incidence and mortality rates (ASIR and ASMR) and the estimated annual percentage change (EAPC), meanwhile, employed Joinpoint regression model to assess the trends. The age-period-cohort model was applied to estimate the effects of the age, period, and cohort on the incidence and mortality. Finally, future asthma trends for the next 25 years were predicted utilizing the Bayesian age-period-cohort (BAPC) model.ResultsOver the past three decades, the incidence rate declined in waves while the mortality declined steadily. The ASIR of asthma decreased from 524.81 to 364.17 and the ASMR declined from 5.82 to 1.47. ASIR and ASMR are consistently higher in males than females during this period. The effect attributable to age on incidence was higher for the younger age group while the mortality was higher for older. The period ratio rate of incidence and mortality declined with the calendar year, and the corrections between birth cohort and the risk of incidence and mortality were negative. Our projections indicate that the ASIR and ASMR will continue to decrease by 2046, with expected rates of 330 and 0.69, respectively. Instead, the absolute number of asthma incidence cases and deaths may increase to approximately 4.5 million and 80,000, respectively.ConclusionAlthough asthma incidence rates and mortality have generally declined in China, the burden remains significant, especially among vulnerable groups, with higher rates in males. Continuous monitoring and age-targeted interventions are essential. Future healthcare strategies must address the aging population to manage the projected increase in asthma cases and deaths.